Bridging the Gap: Exploring the Social and Economic Dimensions of Gender Equality - Priti Gupta; Sanghati Mutsuddi; Renu Kaushik (Recent Trends in Social Studies, 2026)
Gender equality is a fundamental human right and a critical prerequisite for sustainable social and economic development. Despite notable progress in recent decades, significant disparities persist worldwide, particularly in the social and economic domains. This paper explores the multifaceted nature of gender inequality, examining how structural, cultural, and institutional barriers continue to shape unequal access to resources, opportunities, and decision-making power. By analysing key sectors such as education, healthcare, labour markets, and political representation, the study highlights how gender disparities perpetuate intergenerational cycles of poverty, limit human capital development, and constrain economic growth. It emphasises the intersectional nature of gender inequality, illustrating how factors such as class, race, and geography exacerbate disparities and require nuanced, context-specific solutions. The research also evaluates policy interventions and global frameworks aimed at promoting gender parity, arguing that piecemeal efforts are insufficient without comprehensive, inclusive, and sustained strategies. Bridging the gender gap has transformative potential: it can significantly boost economic productivity, foster innovation, improve social cohesion, and advance broader development goals. The paper concludes that achieving gender equality is not only a moral imperative but also an economic necessity and a strategic investment in human potential. Empowering women and ensuring equal participation across all sectors will drive sustainable growth and create more equitable, resilient societies.
Keywords: Education and Gender; gender disparities; gender equality; leadership; skill; social justice